2009
DOI: 10.1111/j.1365-2559.2008.03202.x
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal of synchronous and multifocal mucinous lesions of the female genital tract: a close association with gastric metaplasia

Abstract: There is a close association between SMMN-FGT and LEGH/PGM. Microinvasion and positive peritoneal cytology may not have an influence on outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
80
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(81 citation statements)
references
References 22 publications
1
80
0
Order By: Relevance
“…In some cases, this has been interpreted as representing transtubal spread from the neoplasm within the cervix 1. It is also possible that in some cases this represents mucinous metaplasia of the fallopian tube epithelium since this has been described in Peutz Jeghers syndrome without adenoma malignum 34 35. The second interesting feature is that chromogranin positive neuroendocrine cells were present within the neoplastic glands in the well differentiated component; argyrophilic cells have been described previously in adenoma malignum 1…”
Section: Discussionmentioning
confidence: 79%
“…In some cases, this has been interpreted as representing transtubal spread from the neoplasm within the cervix 1. It is also possible that in some cases this represents mucinous metaplasia of the fallopian tube epithelium since this has been described in Peutz Jeghers syndrome without adenoma malignum 34 35. The second interesting feature is that chromogranin positive neuroendocrine cells were present within the neoplastic glands in the well differentiated component; argyrophilic cells have been described previously in adenoma malignum 1…”
Section: Discussionmentioning
confidence: 79%
“…These authors also found a molecular-genetic link between LEGH and cervical mucinous glandular malignancies, including MDA and MAC, and suggested that some LEGH lesions are precursors of MDA and/or MAC lesions. A close association between synchronous mucinous metaplasia and neoplasms of the female genital tract (SMMN-FGT) and LEGH/pyloric gland metaplasia (PGM) was verified by Mikami et al [24], and Ichimura et al [16] consider MDA to be a malignant conversion of endocervical glands now expressing gastric mucin. They also suggest that the expression level of p53 may be an indicator of the local progression of MDA.…”
Section: Discussion and Reviewmentioning
confidence: 91%
“…This is clearly seen in STK-11 gene mutations, especially in patients with Peutz–Jeghers syndrome,45 where EMM occurs as a spectrum of histological changes ranging from metaplasia to carcinoma, involving synchronously cervix, corpus, fallopian tube and ovary. Multifocality, however, can also occur sporadically 41 43…”
Section: Epithelial Emcsmentioning
confidence: 99%